Comparative genomics reveals adaptations of a halotolerant thaumarchaeon in the interfaces of brine pools in the Red Sea - Kamanda Ngugi, David (ISME J, 2015)
The bottom of the Red Sea harbors over 25 deep hypersaline anoxic basins that are geochemically distinct and characterized by vertical gradients of extreme physicochemical conditions. Because of strong changes in density, particulate and microbial debris get entrapped in the brine-seawater interface (BSI), resulting in increased dissolved organic carbon, reduced dissolved oxygen toward the brines and enhanced microbial activities in the BSI. These features coupled with the deep-sea prevalence of ammonia-oxidizing archaea (AOA) in the global ocean make the BSI a suitable environment for studying the osmotic adaptations and ecology of these important players in the marine nitrogen cycle. Using phylogenomic-based approaches, we show that the local archaeal community of five different BSI habitats (with up to 18.2% salinity) is composed mostly of a single, highly abundant Nitrosopumilus-like phylotype that is phylogenetically distinct from the bathypelagic thaumarchaea; ammonia-oxidizing bacteria were absent. The composite genome of this novel Nitrosopumilus-like subpopulation (RSA3) co-assembled from multiple single-cell amplified genomes (SAGs) from one such BSI habitat further revealed that it shares ∼54% of its predicted genomic inventory with sequenced Nitrosopumilus species. RSA3 also carries several, albeit variable gene sets that further illuminate the phylogenetic diversity and metabolic plasticity of this genus. Specifically, it encodes for a putative proline-glutamate ‘switch' with a potential role in osmotolerance and indirect impact on carbon and energy flows. Metagenomic fragment recruitment analyses against the composite RSA3 genome, Nitrosopumilus maritimus, and SAGs of mesopelagic thaumarchaea also reiterate the divergence of the BSI genotypes from other AOA.